Epistemologi Islam Menurut Ibn Khaldun - Saari, Che Zarrina; Hj. Ab. Majid, Mohd. Kamil (Jurnal Usuluddin, 2000)
The aim of this article is to gather information about Ibn Khaldun's life. His thought on epistemological aspects in his Muqaddimah is also discussed in order to highlight his contribution to the world of knowledge.